Uncivilization in William Shakespeare’s Play The Tempest: Deconstructive Criticism - Sri Wulan (Proceedings of AICS - Social Sciences, 2017)
This paper tries to apply a kind of criticism; that is, deconstruction. In this paper, the kind of criticism is applied to the play entitled The Tempest by William Shakespeare. Deconstruction is a term coined by the contemporary French philosopher Jacques Derrida and it has been used primarily to designate the mode of literary criticism practice since the publication of Derrida’s seminal work in the late 1960’s, by proving more forth coming with negative rather than positive analyses of the school. This criticism tries to examine binary opposition by showing the negative side of the play which implicitly symbolizes the author. Thus, this study also tries to present the negative side in The Tempest, and this negative side refers to uncivilization in this play. There are some civilized but nasty characters that show harshness especially in speech. Although some come from so-called civilized people as they are from high class-society. They often tend to establish impolite ways of speaking, like mocking others, rudeness, insensitivity, and impolite utterances. These forms of harshness in speech actually symbolize uncivilized side. That is why such harshness in speech in William Shakespeare’s play The Tempest becomes the concern of this study. In addition, it seems that such forms of harshness and impolite utterances can be found in the play and those symbolize uncivilization aspect in the play. Keywords:deconstruction, harshness, uncivilized, binary opposition.